Pazzolanic properties of hydrothermal silica gel extracted from sugarcane bagasse using eco-friendly approach - Rahimah, Embong (2016)
In the production of sustainable concrete, it is quite essential to develop highly reactive silica rich materials to substitute cement. Sugarcane bagasse ash as one of the agricultural based pozzolan gained less popularity due to its relatively low amorphous silica content after incineration process (< 50% silica). Therefore, an alternative approach was studied in this research to extract high proportion of amorphous silica from sugarcane bagasse that fulfils the minimum requirement of pozzolanic standard. The process was divided into three stages, which were obtaining optimum pre-treatment variables, obtaining optimum burning variables, and substantiation of pozzolanic feature. Pre-treatment variables were done to remove all impurities and deleterious material from the ash. It involved soaking of bagasse in different concentration of hydrochloric acid solution (0.1M, 0.5M and 1.OM) for different interval of time (1,2 and 3 hours) after which it was dried in a dedicated solar drying chamber for 48 hours. The optimum combination of hydrochloric acid concentration and soaking time was identified based on atomic absorption spectroscopy and x-ray fluorescence. Bagasse treated with optimum parameter would then undergo burning process with various temperatures (600,700 and 800°C) and durations (1, 2 and 3 hours). The produced ash was characterized by determining its oxides composition, particle size analysis, specific surface area, pore volume, mineralogical characteristics and micro-structure using xray fluorescence, x-ray diffraction and field emission scanning electron microscope, respectively. 0.1 M has emerged as the best concentrations with the extraction of silica could reach 83-89% with 1 hour soaking duration. 1 hour burning at 800°C concluded as the most feasible in producing amorphous state of ash. The ash obtained with optimum parameters was amorphous, chemically stable, and ultra-fine. The optimum ash was tested for its pozzolanic reactivity and indicated quite high pozzolanic reactivity index, which contributed to the significant improvement on the compressive strength properties of cementitious mortar of untreated, treated and silica gel at 2.5 and 5% replacement.